Binucleate Rhizoctonia sp AG G causing root rot in yacon (Smallanthus sonchifolius) in Brazil - Fenille, R. C.; Ciampi, M. B.; Souza, N. L.; Nakatani, A. K.; Kuramae, E. E. (Blackwell Publishing, 2005)
A new rot caused by a binucleate Rhizoctonia sp. affecting the tuberous root cortex of the domesticated yacon (Smallanthus sonchifolius) has been observed in Brazil. Isolates of a binucleate Rhizoctonia sp. were collected from roots with rot symptoms and characterized by the number of nuclei per cell, hyphal anastomosis, RAPD molecular markers, ITS-5.8S rDNA sequence and pathogenicity tests. All isolates had a mean of 1.9-2.2 nuclei per cell and anastomosed with the binucleate Rhizoctonia sp. AG G-tester strain. RAPD analysis was carried out between 11 isolates recovered from yacon and 11 AG (A, Ba, Bb, Bo, C, D, F, G, O, P, Q) standard testers of binucleate Rhizoctonia sp. Genetic similarities of 94.8-100% were observed among isolates of the binucleate Rhizoctonia sp. from yacon and all isolates were genetically more closely related to the AG G tester than other strains according to UPGMA analysis using RAPD markers. Homologies of complete ITS nucleotide sequences were 100% between binucleate isolates of Rhizoctonia sp. from yacon and the AG G tester. According to pathogenicity tests, the isolates caused typical rot symptoms of yacon tubers 90 days after inoculation.
Keywords: anastomosis grouping; ITS; RAPD; rDNA